2015
DOI: 10.4253/wjge.v7.i6.665
|View full text |Cite
|
Sign up to set email alerts
|

Metallic stent insertion with double-balloon endoscopy for malignant afferent loop obstruction

Abstract: Progress in double-balloon endoscopy (DBE) has allowed for the diagnosis and treatment of disease in the postoperative bowel. For example, a short DBE, which has a 2.8 mm working channel and 152 cm working length, is useful for endoscopic retrograde cholangiopancreatography in bowel disease patients. However, afferent loop and Roux-limb obstruction, though rare, is caused by postoperative recurrence of biliary tract cancer with intractable complications. Most of the clinical findings involving these complicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…During a PubMed search, we found 12 reports (23 patients) on the use of SEMS to treat malignant ALO that arises after PD (Table 3). [5][6][7][8][9][10][11][12][13][14][15][16] Clinical success was achieved in all cases, and no adverse events were encountered. Although the data were limited, no cases of SEMS obstruction were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During a PubMed search, we found 12 reports (23 patients) on the use of SEMS to treat malignant ALO that arises after PD (Table 3). [5][6][7][8][9][10][11][12][13][14][15][16] Clinical success was achieved in all cases, and no adverse events were encountered. Although the data were limited, no cases of SEMS obstruction were found.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the use of balloon-assisted endoscopy during SEMS placement for malignant ALO has been reported. 4,7,9,[11][12][13][14]16 Shimatani et al reported a case in which SEMS placement was used to treat ALO caused by cancer recurrence after PD, in which a newly developed, shorttype, double-balloon endoscope (S-DBE) (EI-580BT; Fujifilm, Tokyo, Japan) was used. 13 They claimed that the combined use of the new S-DBE, which had a 3.2-mm working channel, and SEMS with a 9 Fr delivery system enabled through-the-scope SEMS placement, which had been previously challenging because the large diameter of the SEMS delivery system did not allow stent deployment through the 2.8-mm working channels of the conventional S-DBE.…”
Section: Discussionmentioning
confidence: 99%
“…Conventional DBE could never allow gastrointestinal metal stent placement for malignant gastrointestinal obstruction such as an afferent-loop obstruction, because of the narrow working channel of the scope. Therefore, one common practice is to insert the conventional DBE to the stricture and subsequently remove it, leaving the overtube; the self-expandable metal stent is then placed through the over-tube under fluoroscopic guidance 7,8. This technique is useful, but stent placement using the new scope, and the through-the-scope method, as in our case, is more ideal for achieving correct and safe stent placement 9…”
Section: Discussionmentioning
confidence: 89%
“…Several cases involving the endoscopic placement of an SEMS for malignant ALO have been reported since the development of DBE- and TTS-type SEMSs ( 2 - 5 ). A few reports have described a combined method in which a DBE is used with an overtube because the large diameter of the SEMS delivery system does not allow for stent deployment through the 2.8-mm working channel of a conventional short DBE ( 2 , 3 ). However, the combined use of the new short-type DBE with a 3.2 mm working channel and TTS SEMS enables easy SEMS placement ( 5 ).…”
Section: Discussionmentioning
confidence: 99%